The long path to achieving green economy performance for micro small medium enterprise - Pangarso Astadi; Sisilia Kristina; Setyorini Retno; Peranginangin Yahya; Awirya Agni Alam (Journal of Innovation and Entrepreneurship, 2022)
Micro small medium enterprises (MSMEs) play an important role in a country's economy, so managers must try to run their business according to the current concept of the green economy (GE). Green economy is an economic concept that makes environmental sustainability an important part of realizing sustainable development goals (SDGs). The performance of MSMEs in terms of GE is a measure of how successful an MSME is in implementing the GE concept. Apart from GE, an equally important element regarding MSMEs is business digitization/digitalization. In the era of society 5.0, MSMEs are increasingly affected by digital technology while running their business. With digitalization, MSME managers can run their company in a more environmentally friendly way to align with the GE concept. Not all MSMEs are ready to implement the GE concept and digitalization, which is a serious problem that deserves attention. To produce a tangible solution related to the implementation of the GE concept and digitization requires a literature review. The literature review helps identify research gaps and formulate a theoretical process in terms of MSME readiness regarding the implementation of the GE concept and digitalization to the performance of GE MSMEs. There is still a limited research framework that comprehensively explains the readiness process related to the GE concept. The digitization of MSMEs on GE's performance is the background of this research. This study aims to develop a research framework for GE MSME performance related to MSME readiness related to the GE concept and digitalization. The research method uses a literature review, and summative content analysis for secondary data in Scopus indexed scientific research publication documents in English, which can be downloaded and relevant until March 2021. The research framework formed consists of 15 constructs for 15 propositions derived from 16 publication documents, using Scopus indexed articles. This research framework contributes to the study of entrepreneurship in general and GE's performance for MSMEs. The research framework formed because of the findings of this study is helpful as a basis for empirical research in the future.
Keywords: 650; Digitalization; Green economy; Innovation; MSME; Quintuple helix